Multivariate Dynamic Sneak-Out Inequalities on Time Scales - Ammara Nosheen; Aneeqa Aslam; Khuram Ali Khan; Khalid Mahmood Awan; Hamid Reza Moradi (Journal of Mathematics)
In this study, we extend some “sneak-out” inequalities on time scales for a function depending on more than one parameter. The results are proved by using the induction principle and time scale version of Minkowski inequalities. In seeking applications, these inequalities are discussed in classical, discrete, and quantum calculus.